2016
DOI: 10.1021/acs.biochem.6b00639
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Conserved Active Site Residues in the Ketosynthase Domain of an Assembly Line Polyketide Synthase

Abstract: Ketosynthase (KS) domains of assembly line polyketide synthases (PKSs) catalyze intermodular translocation of the growing polyketide chain as well as chain elongation via decarboxylative Claisen condensation. The mechanistic roles of ten conserved residues in the KS domain of Module 1 of the 6-deoxyerythronolide B synthase were interrogated via site-directed mutagenesis and extensive biochemical analysis. Although the C211A mutant at the KS active site exhibited no turnover activity, it was still a competent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 19 publications
(76 reference statements)
1
62
0
Order By: Relevance
“…Chemie Zuschriften E. coli FabB also resulted in moderate to very low turnover of the substrate. [17,18] Ad ouble mutant (H3364A and H3404A) stalled the formation of 5,thus proving that these residues are indispensable for the Michael addition. According to functional studies with homologous KS domains, [17][18][19] H3404 activates the malonyl carboxylate and stabilizes the enolate.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Chemie Zuschriften E. coli FabB also resulted in moderate to very low turnover of the substrate. [17,18] Ad ouble mutant (H3364A and H3404A) stalled the formation of 5,thus proving that these residues are indispensable for the Michael addition. According to functional studies with homologous KS domains, [17][18][19] H3404 activates the malonyl carboxylate and stabilizes the enolate.…”
Section: Methodsmentioning
confidence: 94%
“…[17,18] Ad ouble mutant (H3364A and H3404A) stalled the formation of 5,thus proving that these residues are indispensable for the Michael addition. According to functional studies with homologous KS domains, [17][18][19] H3404 activates the malonyl carboxylate and stabilizes the enolate. Reduction of the rates in the carbon-carbon bond formation as well as lactonization ( Figure 2C and 3A,v )i ndicates that H3404 plays am ajor role in all steps of the reaction.…”
Section: Methodsmentioning
confidence: 94%
“…Despite these differences, a S315A mutation in loop 2 of DEBS KS1 increased the formation of propionate, which results from the decarboxylation of the methylmalonyl-ACP substrate. 46 These findings suggest an impaired 14 gating system, like that of the F400A mutant of SpFabF, that can no longer coordinate substrate transfer and C-C bond formation in the correct order. While gatekeeping elements appear to be a general feature of condensing enzymes based upon primary sequence analysis, a more precise stereochemical understanding of these elements will require further biochemical, structural, and computational interrogation.…”
Section: Additionally Ligand-bound and Acyl-enzyme Intermediate Ks Smentioning
confidence: 99%
“…A report on bacterial fatty acid synthases (FabF) suggested that the H3364 counterpart is not an absolute necessity for the C−C bond‐forming reaction, but enhances the overall rate of the reaction . Analogous mutations of the catalytic His residues of the KS of 6‐deoxyerythronolide B synthase (DEBS) module 1 and E. coli FabB also resulted in moderate to very low turnover of the substrate . A double mutant (H3364A and H3404A) stalled the formation of 5 , thus proving that these residues are indispensable for the Michael addition.…”
Section: Figurementioning
confidence: 99%
“…A double mutant (H3364A and H3404A) stalled the formation of 5 , thus proving that these residues are indispensable for the Michael addition. According to functional studies with homologous KS domains, H3404 activates the malonyl carboxylate and stabilizes the enolate. Reduction of the rates in the carbon–carbon bond formation as well as lactonization (Figure C and A, v) indicates that H3404 plays a major role in all steps of the reaction.…”
Section: Figurementioning
confidence: 99%